The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cne.24979
|View full text |Cite
|
Sign up to set email alerts
|

Modeling human‐specific interlaminar astrocytes in the mouse cerebral cortex

Abstract: Astrocytes, a highly heterogeneous population of glial cells, serve as essential regulators of brain development and homeostasis. The heterogeneity of astrocyte populations underlies the diversity in their functions. In addition to the typical mammalian astrocyte architecture, the cerebral cortex of humans exhibits a radial distribution of interlaminar astrocytes in the supragranular layers. These primate-specific interlaminar astrocytes are located in the superficial layer and project long processes traversin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…• Transporter expression (e.g., GLAST) • Ion channel expression (e.g., Kir4.1) • Gap junctional coupling (e.g., Cx43) • Ca 2+ signaling (e.g., hippocampus vs. striatum) • Metabolism • Structural properties (e.g., GFAP expression, spine coverage) Chai et al, 2017;Fernández-Moncada et al, 2021;Herde et al, 2020;Hirrlinger et al, 2008;Kelley et al, 2018;Köhler et al, 2021;Köhler et al, 2018;Kronschläger et al, 2021;Miller et al, 2019;Oheim et al, 2018;Olsen et al, 2007 used to study primate-specific interlaminar astrocytes in mice (Padmashri et al, 2021). Strikingly, grafting human astrocytes into the mouse forebrain enhanced synaptic plasticity and learning (Han et al, 2013).…”
Section: Computational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…• Transporter expression (e.g., GLAST) • Ion channel expression (e.g., Kir4.1) • Gap junctional coupling (e.g., Cx43) • Ca 2+ signaling (e.g., hippocampus vs. striatum) • Metabolism • Structural properties (e.g., GFAP expression, spine coverage) Chai et al, 2017;Fernández-Moncada et al, 2021;Herde et al, 2020;Hirrlinger et al, 2008;Kelley et al, 2018;Köhler et al, 2021;Köhler et al, 2018;Kronschläger et al, 2021;Miller et al, 2019;Oheim et al, 2018;Olsen et al, 2007 used to study primate-specific interlaminar astrocytes in mice (Padmashri et al, 2021). Strikingly, grafting human astrocytes into the mouse forebrain enhanced synaptic plasticity and learning (Han et al, 2013).…”
Section: Computational Analysismentioning
confidence: 99%
“…One approach to studying human astrocyte diversity and its impact on brain circuit physiology has been to transplant stem or progenitor cell-derived human astrocytes into the rodent brain ( Chen et al., 2015 ; de Majo et al, 2020 ; Goldman et al, 2015 ). A similar approach has been used to study primate-specific interlaminar astrocytes in mice ( Padmashri et al, 2021 ). Strikingly, grafting human astrocytes into the mouse forebrain enhanced synaptic plasticity and learning ( Han et al, 2013 ).…”
Section: Challenges In Interpreting Astrocyte Functionmentioning
confidence: 99%
“…The smaller brains, such as those of rodents, do not show these, although astrocytes at the pial surface are also CD44+, as are white matter astrocytes (our unpublished observations). That the morphology is species dependent is implied by studies that produce long-process astrocytes in the mouse after transplanting human induced pluripotent stem cells into the mouse cortex [17], suggesting that human long-process astrocytes are intrinsically programmed to assume this morphology.…”
Section: Interlaminar Astrocytesmentioning
confidence: 99%
“…This chimeric mouse model helped elucidate the glial contribution to Huntington's disease [110] and schizophrenia [111]. It was recently demonstrated that engraftment of immature astrocytes derived from hiPSCs into the mouse cortex resulted in the development of typical interlaminar astrocytes [112]. As a subtype of primate-exclusive astrocytes, the role of interlaminar astrocytes in the brain during physiological and pathological conditions has not been well studied.…”
Section: Generation Of Hipsc-astrocytesmentioning
confidence: 99%
“…The differentiation of astrocytes within brain organoids, which are typically cultured for months, can better model the maturation of hiPSC-astrocytes in vitro [160]. Long-term cultivation could also be accomplished by engrafting hiPSC-astrocytes into the mouse brain, generating cell types that are not seen in 2D cultures [112]. Both the organoid and chimera approaches have the advantage of hiPSC-differentiated astrocytes growing adjacent to and in communication with other cell types.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%